Migrantska kriza i djelovanje međunarodnih organizacija / The Migration Crisis and the Operations of International Organizations - Borić, Nežla (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
From 2015 to 2017 the world saw one of the biggest refugee crises from the Middle East because of this there came a need for the action, and the operation of the International Committee of the Red Cross. The ICRC was originally founded in 1863 with a mandate to help refugees, and internally displaced person. The ICRC played a significant role in the assistance of the record number of refugees, that has been recorded in the history of international law. In the first part of the article the focus is on the basic documents of international law, and the articles regarding legal protection of refugees, and internally displaced persons. Specifically, elaborating on the legal documents, resolutions, and agreements that make up the political actions, and operations of the International Committee of the Red Cross with regards to the refugees, and internally displaced persons. Furthermore, the article discusses the division of responsibility between the UN High Commissioner for Refugees (UNHCR), and the International Committee of the Red Cross (ICRC) since parallel responsibility exists between the two organization towards refugees, and internally displaced persons with regards to international law. The latest refugee crisis is today one of the most important, and most talked about issues of international law. It is stretching out to have a global dimension with an emphasis on resolving this crisis in a humanitarian aspect.